PENGARUH LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN PADA PLAZA MEBEL FURNITURE CENTER PEKANBARU - Annisa, Kiki; Andri, Seno (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine how much influence the work environment and compensation on employee job satisfaction. The sample in this study was taken as many as 72 respondents and the technique used was Total Sampling. The data in this study used the survey method through questionnaires filled out by employees. Data obtained using simple regression analysis and multiple regression analysis. The results of this study indicate that the work environment has a significant effect on job satisfaction. compensation has a significant effect on job satisfaction. And simultaneously the work environment and compensation have a significant effect on employee job satisfaction. Further research is recommended to use other methods in examining job satisfaction, for example through in-depth interviews with respondents. Keywords: Work Environment, Compensation, and Job Satisfaction